Disorganized Gut Microbiome Contributed to Liver Cirrhosis Progression: A Meta-Omics-Based Study - Shao, Li; Ling, Zongxin; Chen, Deying; Liu, Yufeng; Yang, Fengling; Li, Lanjuan (Frontiers in Microbiology, 2018)
Early detection and effective interventions for liver cirrhosis (LC) remain an urgent unmet clinical need. Inspired from intestinal disorders in LC patients, we investigated the associations between gut microbiome and disease progression based on a raw metagenomic dataset of 47 healthy controls, 49 compensated and 46 decompensated LC patients from our previous study, and a metabolomic dataset of urine samples from the same controls/patients using ultra-performance liquid chromatography/mass spectrophotometry system. It was found that the combination and relative abundance of gut microbiome, the inter-microbiome regulatory networks, and the microbiome-host correlation patterns varied during disease progression. The significant reduce of bacteria involved in fermentation of plant cell wall polysaccharides and resistant starch (such as Alistipes sp. HG5, Clostridium thermocellum) contributed to the reduced supply of energy sources, the disorganized self-feeding and cross-feeding networks and the thriving of some opportunistic pathogens in genus Veillonella. The marked decrease of butyrate-producing bacteria and increase of Ruminococcus gnavus implicated in degradation of elements from the mucus layer provided an explanation for the impaired intestinal barrier function and systematic inflammation in LC patients. Our results pave the way for further developments in early detection and intervention of LC targeting on gut microbiome.